2018
DOI: 10.1016/j.ijmm.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Thioloxidoreductase HP0231 of Helicobacter pylori impacts HopQ-dependent CagA translocation

Abstract: Thioloxidoreductase HP0231 of Helicobacter pylori plays essential roles in gastric colonization and related gastric pathology. Comparative proteomics and analysis of complexes between HP0231 and its protein substrates suggested that several Hop proteins are its targets. HP0231 is a dimeric oxidoreductase that functions in an oxidizing Dsb (disulfide bonds) pathway of H. pylori. H. pylori HopQ possesses six cysteine residues, which generate three consecutive disulfide bridges. Comparison of the redox state of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
8
1
1
Order By: Relevance
“…However, our results indicate that this is independent of HopQ, since the lack of HP0231 did not impair HopQ-CEACAM1 interaction, and thus the binding of H. pylori to epithelial cells. This finding is in contrast to a recent description of the interaction of HP0231 with HopQ, where HP0231 was thought to directly interact with and influence HopQ binding and subsequent CagA translocation [23]. The discrepancy in strains used or assay formats could explain the contrasting findings we observed, though in our assays we found that ∆hp0231 mutants in multiple strain backgrounds had no effect on HopQ-mediated binding in several assay settings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, our results indicate that this is independent of HopQ, since the lack of HP0231 did not impair HopQ-CEACAM1 interaction, and thus the binding of H. pylori to epithelial cells. This finding is in contrast to a recent description of the interaction of HP0231 with HopQ, where HP0231 was thought to directly interact with and influence HopQ binding and subsequent CagA translocation [23]. The discrepancy in strains used or assay formats could explain the contrasting findings we observed, though in our assays we found that ∆hp0231 mutants in multiple strain backgrounds had no effect on HopQ-mediated binding in several assay settings.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we demonstrate that the disulfide bond between residues C103 and C132, present in cysteine-clasped loop CL1, is required for CEACAM1 engagement by HopQ, whereas the disulfide bonds present in CL2 and 3are not. This is in contrast to what was reported in a recent paper [23], though consistent with our published co-complex structure [5]. As CL3 is located distant from the binding interface, no negative effect upon disruption of its disulfide is expected.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The recent studies highlighted that the interaction between HopQ and CEACAM contributes to gastric colonization [114] and facilitates translocation of the CagA protein into the gastric epithelium to induce pathogenicity [114,116,121,122]. A recent study showed that the interaction between HopQ and CEACAM plays a significant role in inhibiting immune cell activities [40].…”
Section: Virulence Factors Associated With Colonization Of Epithelmentioning
confidence: 99%
“…An H. pylori strain lacking the major Dsb oxidoreductase, encoded by hp0231, is deficient in CagA translocation into host epithelial cells as Hp0231, among other activities, influences the structure of HopQ, an outer membrane protein that mediates pathogen adhesion to epithelial cells by interaction with CECAM receptors (Javaheri et al 2016;Königer et al 2016). Lack of Hp0231 abolishes the H. pylori-induced IL-8 production and the development of the hummingbird phenotype in AGS cells (Zhong et al 2016;Grzeszczuk et al 2018). Moreover, an H. pylori hp0231-deficient strain was not able to colonize the gastric mucosa of mice.…”
Section: Targeting Virulence Factors Of H Pylorimentioning
confidence: 99%